ANALISIS TEGANGAN PADA ELBOW PIPE SA 123 Gr.T22 DI SHELL AND TUBE HEAT EXCHANGER - Abdul Haris Siregar; Hary Sutjahjono; Agus Triono (ROTOR, 2019)
Heat exchanger is a system used to transfer heat between fluids. The most cases of heat exchanger failure is leakage pipe. This study aims to see the effect of increasing the radius of the elbow pipe in the shell and tube heat exchanger on the stress due to internal and external pressure. The research using ANSYS 15 at elbow pipe radius 40 mm, 51 mm and 62 mm with internal pressure 20.4 MPa and external pressure 2.04 MPa. Obtained maximum results occur in 40 mm radius elbow pipe of 81,528 MPa and minimum result occurs in 62 mm of 76,212 MPa. The stress that occurs in all elbow pipe can be said safe because the stress value is still under the pipe material yield point.